Analysis of enterolignan glucuronides in serum and urine by HPLC-ESI-MS - Knust, Ulrike; Hull, William Edmund; Spiegelhalder, Bertold; Bartsch, Helmut; Strowitzki, Thomas; Owen, Robert (Food and chemical toxicology, 2006)
A method involving the coupling of high-performance liquid chromatography with electrospray ionisation mass spectrometry (HPLC-ESI-MS) for the quantitative determination of the mammalian lignans enterolactone and enterodiol in human blood and urine has been developed. In contrast to techniques previously published, the method allows direct measurement of free enterolignans as well as their monoglucuronide conjugates in human biofluids with minimal sample preparation. Thereby the method is suitable for large-scale intervention, case-control and epidemiologic studies. Comprehensive, high-precision 1H and 13C nuclear magnetic resonance data (CD3OD as solvent) obtained at 11.7T in combination with polarimetric data show that the major form of lignan precursor in the linseeds used is (−)-secoisolariciresinol diglucoside ((2R,3R)-2,3-bis(4′-hydroxy-3′-methoxy-benzyl)-1,4-butanediyl-bis-β-d-glucopyranoside) which is transformed by human intestinal bacteria into (+)-enterodiol and (+)-enterolactone. However, these metabolites are mono-glucuronidated after absorption and are detected as (−)-enterodiol 3′-β-d-glucuronide=(2R,3R)-2-(3′-O-(β-d-glucopyranosyluronic acid)benzyl)-3-(3″-hydroxybenzyl)-butane-1,4,diol and (−)-enterolactone 3′-β-d-glucuronide=(2R,3R)-2-(3′-O-(β-d-glucopyranosyluronic acid)benzyl)-3-(3″-hydroxybenzyl)-β-butyrolactone in blood and urine.
Gesehen am 23.11.2020